The first characterized carbapenem-resistant Bacteroides fragilis strain from Croatia and the case study for it - Bogdan Maja (ACTA MICROBIOLOGICA ET IMMUNOLOGICA HUNGARICA, 2018)
An imipenem-resistant Bacteroides fragilis strain was isolated from the blood of a 72-year-old male patient with a urinary bladder tumor in Osijek, Croatia. This strain was also resistant to ampicillin, piperacillin/tazobactam, cefoxitin, clindamycin, tetracycline, and harbored cfiA, ermF, and tetQ genes where the high-level expression of the cfiA carbapenem-resistant gene was driven by an IS1187 element. Interestingly, despite the carbapenem-resistant feature of the B. fragilis from blood, the patient relatively easily recovered from the bacteremia. It was the first characterized imipenem-resistant B. fragilis isolate with its case report from Croatia, which confirmed the appearance of carbapenem-resistant B. fragilis strains, that continues worldwide with low incidence and the molecular characteristics vary temporally and geographically.